resolva a equação 3(2x-1)=2(x+5)
Soluções para a tarefa
Respondido por
0
6X-3=2X+10
6X-2X=10+3
4X=13
X= aproximadamente 3
6X-2X=10+3
4X=13
X= aproximadamente 3
Respondido por
0
resolva a equação 3(2x-1)=2(x+5)
3(2x+1)=2(x+5)
6x-3=2x+10
6x-2x=10+3
2x=13
X=13/2
Espero ter ajudado
3(2x+1)=2(x+5)
6x-3=2x+10
6x-2x=10+3
2x=13
X=13/2
Espero ter ajudado
Perguntas interessantes
Matemática,
11 meses atrás
Biologia,
11 meses atrás
Geografia,
11 meses atrás
História,
1 ano atrás
Matemática,
1 ano atrás
Geografia,
1 ano atrás
Sociologia,
1 ano atrás
Matemática,
1 ano atrás